Konsep Hak Milik Menurut Islam, Kapitalis dan Sosialis: Sebuah Komparasi - Subroto Subroto (Justicia Islamica, 2004)
This study aims to compare the concept of property rights in the perspectives of Islam, capitalism, and socialism in order to understand the fundamental differences and their implications in the economic and legal systems. The method used is normative juridical research with a comparative law approach. Data were obtained through a literature study that included religious literature, economic theory, and related regulations. The results showed that in Islam, property rights are individual but limited by social interests and justice. Capitalism emphasizes private ownership without significant restrictions, while socialism emphasizes collective ownership for the sake of social equality. This comparison reveals that the Islamic system offers a balance between individual ownership and the public interest, in contrast to the extreme approaches of capitalism and socialism. Therefore, the concept of property rights in Islam has the potential to become a fairer alternative model for resource management.